Can a patient reported outcome be adequate without assessing quality of life in lower urinary tract dysfunction?. Issue 4 (April 2017) - Cotterill, Nikki; Tubaro, Andrea
Abstract : AIMS AND METHODS: A think tank was convened at the sixth ICI‐RS meeting held in the United Kingdom on September 2015, to consider the adequacy of patient reported outcome (PRO) measurement if quality of life (QoL) evaluation were excluded. Rigorous methodology is proposed for the development of PROs and much is written about this process but the necessity for QoL inclusion is rarely discussed. The decision was therefore taken to consider what QoL evaluation provides and what these data provide. RESULTS: Discussions highlighted the need to question our aim for including QoL evaluation in clinical practice and research, in order to ensure its necessity for the intended purpose. Improved understanding of the usefulness of QoL data, in particular in relation to important health indicators was also identified as an area of unmet need. CONCLUSIONS: The think tank ended with a collaborative research proposal to pool existing QoL databases to explore the correlations with other outcome measures and types of associations present. It was suggested that these findings would enable clinicians and researchers to make more informed decisions regarding PRO selection, use, and intepretation.